Translation and adaptation to Spanish of Aberdeen varicose veins questionnaire. (June 2023) - Ibarra Sanchez, Gabriela; Ansuategui Vicente, Marina; Revuelta Suero, Sergio; Cases Perez, Cristina; Comanges Yeboles, Alejandra; Gonzalez Fajardo, Jose Antonio
Objective: The purpose of the study is to translate the Aberdeen Varicose Vein Questionnaire (AVVQ) into Spanish and evaluate the feasibility and reliability of the Spanish-translated AVVQ in patients with chronic venous disease. Methods: Reliability was assessed by test and retest of the Spanish translated AVVQ in a sample of 77 patients. The questionnaires were answered within a 2-week interval. Results: There was a 100% test and retest response. The AVVQ showed 6.5% of missing responses. Cronbach's alpha was 0.71 indicating an adequate level of internal consistency. Spearman's rho showed a significant strong association between test and retest scores (rho = 0.84, p < 0.0001). Conclusions: The Spanish-translated AVVQ is a reliable tool in our daily clinical practice in order to measure the impact of venous disease in the quality of life.